International cooperation of science and technology for developing economy: Lessons from Korea footprint - Kim, Eui-Seong; Lee, Hyeokseong; Won, Yoohyung; Kum, Dongwha (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2018)
Purpose - This paper aims to investigate the development trajectory of Korean economy accompanied with science and technology, and suggest customized development strategy and international technology cooperation plan for a developing country, Vietnam. Design/methodology/approach - This research applies a qualitative analysis to review the economic development history of Korea and Vietnam and the model of supporting the developing countries. From an amount of the reviews, this paper suggests the VietnamKorea technological cooperation plan. Findings and Implications - There are four suggestions for advancement of the technology policy of Vietnam. First, the overall policy direction for the Vietnam 2016-2020 plan lacks individual industry policies. Localization of high-value-added products should be actively pursued within the network of FDI and export supply. Second, Vietnam should move toward manufacturing high-value-added products in order to enter the global value chain with local products, as Korea did in the 1980s. Third, attempts to grow the Vietnamese manufacturing industry should proceed towards actual inspection. Lastly, the authors suggest that Vietnam should cultivate manpower to foster researchers and improve their expertise. Originality/value - There is little research that investigates both development trajectories of Korea and Vietnam, and suggests the modified development strategies for Vietnam. This paper fills this gap.